Performance Comparison of Narrow Bandgap Semiconductor Cells for Photovoltaic and Thermophotovoltaic Applications - Gamel M.M.A.; Ker P.J.; Lee H.J.; Rashid W.E.S.W.A.; Jamaludin M.Z.; Mohammed A.I.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cells; Cytology; Energy gap; Gallium; Gallium arsenide; III-V semiconductors; Indium; Indium arsenide; Infrared radiation; Narrow band gap semiconductors; Photocurrents; Photonics; Semiconducting antimony compounds; Semiconducting germanium; Semiconducting indium; Semiconducting indium gallium arsenide; Semiconductor alloys; Comparative studies; Illumination spectrum; Indium gallium arsenide; Performance comparison; Radiation temperature; Surface recombinations; Thermophotovoltaic applications; Thermophotovoltaics; Solar cells